Uniformly porous PVDF-co-HFP membranes prepared by mixed solvent phase separation for direct contact membrane distillation - Nuaimi, Reham Al; Thankamony, Roshni Lilly; Boross de Levay, Jean-Pierre Benjamin; Yuan, Bingbing; Lai, Zhiping (Journal of membrane science, 2024)
Membrane distillation has gained significant interest as a promising technology for treating high-salt wastewater. However, membranes with large and nonuniform pore structures are prone to wetting, which compromises their salt rejection efficiency. In this study, a highly uniform porous poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) membrane was designed and prepared through the mixed solvent phase separation (MSPS) method, which was utilized in direct contact membrane distillation to treat salt concentration solutions as high as 5.85 wt%. The results showed 13 % polymer concentration, 26 % octane concentration, and 90 s of cooling duration exhibited an optimal structure with an average pore size of 53 ± 3 nm, a surface porosity of 24.79 %, and a liquid entry pressure (LEP) value of 3.5 bar. The optimum MSPS PVDF-HFP membrane demonstrated a vapor flux of 27 kg m−2 h−1 and high salt rejection (more than 99.94 %), superior than that of the controlled NIPS membrane with nonuniform pore sizes and lower surface porosity. This desalination performance is comparable with the commercial PTFE membrane (99.68 %, 29 kg m−2 h−1) featuring an order of magnitude higher pore sizes and greater LEP. Importantly, the MSPS PVDF-HFP membrane maintained its high performance over the duration of a long-term experiment (>140 h). [Display omitted] •Uniformly porous PVDF-HFP membranes were prepared via the MSPS method.•An average pore size of 53 ± 3 nm and a surface porosity of 24.79 % were observed.•A vapor flux of 27 kg m2 h−1 with more than 99.94 % salt rejection was achieved.•The optimum membrane achieves comparable performance to the commercial membranes.